2016
DOI: 10.3747/co.23.3166
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Status and Lifestyle Behaviours in Cancer Survivors: Smoking and Physical Activity

Abstract: Purpose Smoking cessation and increased physical activity (pa) have been linked to better outcomes in cancer survivors. We assessed whether socioeconomic factors influence changes in those behaviours after a cancer diagnosis. MethodsAs part of a cross-sectional study, a diverse group of cancer survivors at the Princess Margaret Cancer Centre (Toronto, ON), completed a questionnaire about past and current lifestyle behaviours and perceptions about the importance of those behaviours with respect to their health.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 54 publications
(60 reference statements)
2
30
1
Order By: Relevance
“…A study by Wong and his associates indicated the incidence and mortality of esophageal cancer is highly correlated with SDI of countries ( 28 ). The economic development of a country determines the patient’s health seeking behavior and lifestyle, access to screening and management options, which in turn impact the survival from esophageal cancer ( 29 , 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study by Wong and his associates indicated the incidence and mortality of esophageal cancer is highly correlated with SDI of countries ( 28 ). The economic development of a country determines the patient’s health seeking behavior and lifestyle, access to screening and management options, which in turn impact the survival from esophageal cancer ( 29 , 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, unemployed survivors were more likely to be found in more symptomatic cluster groups (class 2, class 3, class 4) than those who were employed, and the strongest association between employment status and symptom clusters was found in those with the highest symptom burden (class 4). One plausible explanation is that individuals with higher socioeconomic status, measured as higher education and employment, may be more likely to engage in healthy lifestyle behaviors (e.g., physical activity) (Naik et al, 2016;Park et al, 2015). Those with higher economic status also may be better able to access appropriate healthcare services and communicate with clinicians after treatment has ended, thereby facilitating better symptom management (DiMartino, Birken, & Mayer, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Education also brings resources to improve health behavior including a better social support and a feeling of being in control of one’s life [ 54 ]. Poor education not only has an effect on smoking, alcohol use, salt intake, and other risk behaviors, but also has difficulty in overcoming problems existed in the process of changing behavior, for example, Naik et al found that poor education contributed to continued smoking and continued physical inactivity [ 55 ].…”
Section: Discussionmentioning
confidence: 99%